Checkpoint kinase 1 is activated and promotes cell survival after exposure to sulphur mustard. Issue 2 (22nd January 2015) - Jowsey, Paul A.; Blain, Peter G.
Highlights: ATR-dependent activation of CHK1 after SM. Inhibition of CHK1 increased SM-induced cytotoxicity and apoptosis. Inhibition of CHK1 caused progression into mitosis after SM. Abstract: Sulphur mustard (SM) is a vesicating agent that has been used several times as a weapon during military conflict and continues to pose a threat as an agent of warfare/terrorism. After exposure, SM exerts both acute and delayed long-term toxic effects principally to the skin, eyes and respiratory system. These effects are thought to be mediated, at least in part, by direct interaction of SM with DNA, forming a myriad of DNA lesions and initiating effects on cell cycle and cell death pathways. Previous studies have demonstrated that a complex network of cellular DNA damage response pathways are utilised in cells exposed to SM, consistent with SM causing multiple forms of DNA damage. The present study focused on the role of Checkpoint kinase 1 (CHK1), a protein with putative roles in homologous recombination repair, p53 activation and the initiation of cell cycle checkpoints after certain forms of DNA damage. The data showed that SM caused robust activation of CHK1, monitored by multi-site phosphorylation analysis and that this activation was dependent on the ataxia telangiectasia and Rad3-related (ATR) protein kinase. Furthermore, specific inhibition of CHK1 increased SM toxicity in multiple human cell lines, with concomitant increases in markers of apoptosis, DNA damage and mitosis. Finally, the effect of CHK1 inhibition on SM toxicity was much more marked in cells with non-functional p53.